Evolution of Psychological Contract Research: A Systematic Review and Bibliometric Analysis - Rupam Jyoti Deka, Anil Kumar Srivatav (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The ‘Psychological Contract’ refers to the unwritten expectations and obligations that exist between an employer and employee, beyond the formal contract of employment. The ‘Psychological Contract’ (PC) is not static and may change over time, which makes longitudinal research necessary. This study attempts to analyse the evolution of research conducted on PC and the findings highlighted the existing trends and future research directions of PC with respect to its influence in Organizational Behaviour Research. Design/Methodology/Approach: Contextualized systematic literature review (SLR) and bibliometric techniques are conducted using VOS viewer application and analysis of Elsevier’s Scopus Database search result of total of 653 Articles from Top Quality Journals. Findings: Bibliometrics analysis techniques are used to identify Recent Trends, Total Citations (TC), Top Influential Articles (TIA), Most influential Author and Journals (MIA & MIJ), Top Contributing Institutions and Countries (TCI & TCC) and most significant co-words, keywords, and so on, followed by comprehensively science mapping analysis. The top 10 most widely published journals in the specialised field, as measured by ‘SNIP, SJR, and Cite Scores’, ‘h-Index’ are identified and thoroughly examined. Finally, the research has revealed significant research gaps, which will pave the way to future studies. Research limitations/implications: The scope of the present study and subsequent selection of literature is confined to the areas of Psychological Contract (PC) limited to Articles in "Business, Management and Accounting", "Social Sciences", "Arts and Humanities” from Elsevier’s Scopus Date Base using CSV Excel and VOS viewer software only. Originality/value: The major contribution of this study is presentation of 2 propositions and their subsequent ‘Conceptual Model' derived from the literature on PC. It explores key gaps in research paving the way the scope of future research. Furthermore, the combination of Systematic Literature Review and Bibliometric Analysis is a methodological contribution in this research domain of PC.